Effect of Emotional Intelligence on Delinquents in KPK - Iqbal, Hina; Shafiq, Mohammed; Khayam; Naseer , Rabia (International Journal of Psychosocial Rehabilitation, 2020)
The present study aims at assessing the effect of Emotional intelligence (EI) on delinquents in KPK. For this, a sample of 200(n) adolescents were selected which is comprised of 100(n) Delinquents, selected from Jail of Peshawar and Haripur whereas 100(n) non- delinquents who were selected from different schools of Peshawar and Haripur by keeping age and other demographic same. Before collecting the data on EI, their delinquency was evaluated on Self-Reported Delinquency Scale (SRD) and categorized them into delinquents and non-delinquent’s groups respectively. It was hypothesized that delinquents have impaired EI than non-delinquents. The second hypothesis was to investigate the effect of EI on delinquency. By using the independent sample t-test, delinquents scored significantly low on all the subscales of EI i.e., Emotional self- Acceptance (ESA), Emotional self-Regulation Scale (ESRS) and Interpersonal skills (ISS) AND (p<.001). By using the multiple linear regression model, EI(ESRS, ESA, ISS) significantly affects (p<.001) in the delinquents than non-delinquent subjects. The study concluded that EI significantly affects the severity of delinquency. As EI is a basic psychological component so it affects youth and prone towards delinquency. It is suggested that cognitive behavior therapy could work on EI of delinquents that may enable them to function appropriately in the society.